Valuing users' willingness to pay for improved water quality in the context of the water framework directive. Issue 5 (3rd July 2020) - Lazaridou, D.; Michailidis, A.
ABSTRACT: The Water Framework Directive (WFD) explicitly acknowledges the role of economics in the process of achieving the water quality targets it sets. At the same time, stakeholder participation in water resources management is emphasized in the Directive. In this paper, we examine farmers' willingness-to-pay (WTP) for ecological status improvement at a river basin scale. Based on a Contingent Valuation survey aims first to estimate the value farmers place on water quality improvement as it is envisaged by the WFD. Then through the use of different econometric models it was attempted to address zero responses and to find a robust estimate for the mean WTP. In a sample of more than 300 respondents, we found that 64.57% of them expressed zero responses. Further findings indicate that the mean values irrigators are willing to pay, for reaching the water quality targets set by the Directive, range between 11.5€/ha and 22.0€/ha (on an annual basis). Through the present research, farmers' willingness-to-pay for improvements in water quality directly investigated for the first time in Greece. Therefore, the results are provided can be useful for central decision makers.